2018
DOI: 10.1002/hep4.1192
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 1 regulatory subunit 3B gene variation protects against hepatic fat accumulation and fibrosis in individuals at high risk of nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a major cause of liver damage and has a strong genetic component. The rs4841132 G>A variant, modulating the expression of protein phosphatase 1 regulatory subunit 3B (PPP1R3B), which is involved in glycogen synthesis, has been reported to reduce the risk of NAFLD but at the same time may favor liver disease by facilitating glycogen accumulation. The aim of this study was to assess the impact of rs4841132 on development of histologic steatosis and fibrosis in 1,388 Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…This GCKR variant is also highly associated with fatty liver in obese youths [33]. Recent genetic and epidemiological studies have identified other polymorphisms associated with NAFLD progression in several genes involved in retinol metabolism (hydroxysteroid 17-beta dehydrogenase 3 (HSD17B3)), glycogen synthesis (protein phosphatase 1 regulatory subunit 3B (PPP1R3B)), bile acid homeostasis (beta-klotho (KLB)), oxidative stress (uncoupling protein 2 (UCP2), superoxide dismutase 2 (SOD2)), insulin signaling pathway (tribbles pseudokinase 1 (TRIB1)), and inflammation (suppressor of cytokine signaling 1 (SOCS1), interferon lambda 3 (IFNL3), MER proto-oncogene tyrosine kinase (MERTK)) [12,[34][35][36][37][38][39]. In addition, epigenetic mechanisms, including post-translational histone modifications, DNA methylation, and micro-RNAs, are important in disease development [12].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…This GCKR variant is also highly associated with fatty liver in obese youths [33]. Recent genetic and epidemiological studies have identified other polymorphisms associated with NAFLD progression in several genes involved in retinol metabolism (hydroxysteroid 17-beta dehydrogenase 3 (HSD17B3)), glycogen synthesis (protein phosphatase 1 regulatory subunit 3B (PPP1R3B)), bile acid homeostasis (beta-klotho (KLB)), oxidative stress (uncoupling protein 2 (UCP2), superoxide dismutase 2 (SOD2)), insulin signaling pathway (tribbles pseudokinase 1 (TRIB1)), and inflammation (suppressor of cytokine signaling 1 (SOCS1), interferon lambda 3 (IFNL3), MER proto-oncogene tyrosine kinase (MERTK)) [12,[34][35][36][37][38][39]. In addition, epigenetic mechanisms, including post-translational histone modifications, DNA methylation, and micro-RNAs, are important in disease development [12].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Finally, the rs4841132 G>A variant, enhancing the expression of Protein Phosphatase 1 Regulatory subunit 3B (PPP1R3B), which is involved in glycogen synthesis, has been recently reported to reduce the risk of NAFLD, but at the same time, may favor liver disease by facilitating glycogen accumulation [96,97]. Conversely, in a rodent model, hepatic genetic deletion of PPP1R3B significantly reduced glycogen synthase protein abundance, glucose incorporation into hepatic glycogen, total hepatic glycogen content and fasting plasma glucose compared to wild-type littermates [98].…”
Section: Other Nafld Genetic Risk Factors Responsive To Dietmentioning
confidence: 99%
“…91,92 Similarly, a gene variation at the protein phosphatase 1 regulatory subunit 3b (PPP1R3B) is thought to potentially protect against hepatic fat accumulation and decreases risk of progressive liver disease in patients at high risk for NASH. 93,94 Lastly, the rs12979850 polymorphism in the IFNλ3 gene that participates in regulation of innate immunity has been associated with increased hepatic inflammation and fibrosis in patients with NAFLD, particularly in lean NAFLD. 95,96 Several genetic risk scores have been designed to predict the presence of NASH, NASH with fibrosis and NAFLD-related HCC.…”
Section: Genomicsmentioning
confidence: 99%